2022
DOI: 10.1177/17531934221079182
|View full text |Cite
|
Sign up to set email alerts
|

Palmar approach for fixation of metacarpal fractures

Abstract: Between 2018 and 2020, 14 patients with closed metacarpal fractures requiring open reduction were operated on via a palmar approach. Reduction and fixation were done with screws or plates. We assessed range of motion, grip strength, Mayo score, possible nerve damage and cosmesis. The range of motion and grip strength were fully restored by 6 months after operation. Transient paraesthesiae in the digital nerve territory occurred in two patients and had resolved by 3 months. In selected patients the palmar appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…If necessary, the treatment plan can be adjusted to promote healing. Nazerani et al [6] reported 14 cases with metacarpal fracture who were treated with volar plate fixation the range of motion and grip strength were fully restored within 6 months postoperatively. In general, the activities of daily living do not usually exceed the yield force reported in this study, and the bones at the metacarpal neck are mostly cancellous bones, which have a relatively high healing capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If necessary, the treatment plan can be adjusted to promote healing. Nazerani et al [6] reported 14 cases with metacarpal fracture who were treated with volar plate fixation the range of motion and grip strength were fully restored within 6 months postoperatively. In general, the activities of daily living do not usually exceed the yield force reported in this study, and the bones at the metacarpal neck are mostly cancellous bones, which have a relatively high healing capacity.…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, among all types of metacarpal fractures, metacarpal neck fractures are the most common and the most unstable, with an incidence rate as high as half of all metacarpal fractures. [2][3][4][5][6] In terms of location, the incidence rate of second to fifth metacarpal neck fracture is 88% except in the thumb, and the fifth metacarpal bone is the most common location (also known as a boxer's fracture). [5,7] According to the majority of treatment principles, nondisplaced fractures can be treated conservatively.…”
Section: Introductionmentioning
confidence: 99%